Has Zika been forgotten? A qualitative exploration of knowledge gaps, perceived risk and preventive practices in pregnant women in Malaysia - Li Ping Wong; Haridah Alias; Hai Yen Lee; Sazaly AbuBakar; Yulan Lin; Zhijian Hu (BMC Women's Health, 2024)
Abstract Background Although Zika virus infection is rarely reported now, continuous prevention is needed to achieve sustained eradication. This study aimed to explore the knowledge gaps, risk perception and preventive measures against Zika virus infection (ZIKV) in pregnant women in Malaysia. Methods We conducted in-depth virtual interviews with pregnant women between February and April 2022. The interviews were recorded and transcribed, and data were analyzed by content analysis. Results The majority of the participants demonstrated a commendable level of awareness regarding the signs and symptoms associated with ZIKV infection. They also exhibited a clear understanding of preventive measures, particularly emphasizing the importance of avoiding mosquito bites to minimize the risk of ZIKV transmission. However, a noteworthy gap in knowledge surfaced as a subset of participants remained uninformed about the potential for sexual transmission of ZIKV, which could lead to congenital ZIKV in pregnant women. Even among women who were cognizant of ZIKV and its potential negative health outcomes, associated with the infection, many of them did not perceive themselves to be at risk, mainly because ZIKV infection is infrequently discussed or heard of, leading to a sense of infections’ rarity. While the adoption of preventive measures such as mosquito bite prevention during pregnancy was a common practice, however, prevention of sexually transmitted infections (STIs) including mosquito-borne diseases such as Zika is low. A minority of women express concerns about the sensitivity surrounding discussions and prevention of STIs within the context of marriage. Most of the participants were supportive of the provision of awareness of ZIKV infection in women during pregnancy and the involvement of men, especially in initiatives aimed at preventing transmission through sexual contact. Conclusion This study uncovered gaps in both knowledge and practices pertaining ZIKV infection among pregnant women in the aftermath of the ZIKV pandemic. The insights gleaned from our research are valuable for shaping future interventions geared towards preventing the resurgence or facilitating the sustainable eradication of ZIKV.